Intakes of milk and alternatives among on-reserve First Nations youth in northern and southern Ontario, Canada - Gates, Michelle; Hanning, Rhona M; Gates, Allison; Martin, Ian D; Tsuji, Leonard JS (Public Health Nutrition, 2012)
Abstract Objective To assess the adequacy of milk and alternatives, Ca and vitamin D intakes in First Nations (FN) youth in Ontario, Canada. Intakes were compared with the general population and dietary standards. Variation in intakes by community (proxy for remoteness) and BMI was examined. Design Data were collected by 24 h recall between November 2003 and June 2010. Intakes were analysed descriptively. Variation in intakes, by community and BMI category, was assessed using ANOVA. Setting Five remote FN communities of the Mushkegowuk Territory (northern Ontario, Canada) and two less-remote southern Ontario FN communities. Subjects Schoolchildren ( n 457) in grades 6 to 12. Results Compared with Canada's Food Guide recommendations, 72·6 to 84·7 % had an inadequate intake of milk and alternatives depending on age and sex group; 86·2 % of individuals fell below the RDA for Ca; 96·4 % fell below the RDA for vitamin D. Community variation in intakes was detected, although in all cases Fort Albany had higher intakes, even when it was the more northern (remote) community. A BMI × sex interaction was found for intake of milk and alternatives ( P = 0·041): an inverse relationship between intake and BMI was seen in females; in males, those who were overweight had the highest intake, followed by normal-weight and obese youth. Conclusions The nutritional inadequacies parallel the results of other Canadian studies of Aboriginal populations. Population health interventions to improve intakes are warranted. Moreover, community variation in intakes exists among FN youth in the present study (Fort Albany pairs only), but results were not as expected.